Assessment of Immunological Biomarkers in Diabetic Patients with and without Foot Ulcers - Al-Khalidi , Aseel Abd Ulameer Kamas‏ ‏; Hatem, Rasha Muzahem (International Journal of Basic and Applied Sciences, 2025)
Ulcers of the foot caused by diabetes (DFU) are among the most severe consequences of diabetes mellitus, significantly diminishing ‎patients’ quality of life and often resulting in persistent infections and potential limb loss. This study aimed to assess the serum levels ‎of four immunological biomarkers: interleukin-10 (IL-10), interleukin-18 (IL-18), tumor necrosis factor-alpha (TNF-α), and basic ‎fibroblast growth factor (bFGF) in patients with diabetes and in patients without foot ulcers, as well as in healthy participants. The ‎study enrolled 90 participants, including diabetic patients with foot ulcers, diabetic patients without ulcers, and healthy controls. ‎Then, the Blood samples were collected and analyzed using ELISA to determine serum concentrations of IL-10, IL-18, TNF-α, and ‎bFGF. Statistical analyses included ANOVA, Duncan's multiple range test, and ROC curve evaluation. The results indicate that IL-18 ‎and TNF-α levels were significantly elevated in both diabetic groups compared to controls (P < 0.001), indicating persistent systemic ‎inflammation. IL-10 levels were significantly higher in diabetics without ulcers than in controls (P < 0.05), suggesting a compensatory ‎anti-inflammatory response. Interestingly, bFGF was significantly elevated in patients with ulcers (P < 0.001), potentially reflecting a ‎local reparative response. ROC analysis revealed that bFGF had high diagnostic accuracy (AUC = 0.809) in differentiating DFU ‎patients from healthy individuals. The finding highlighted that the observed cytokine profiles suggest that DFUs are characterized by ‎an inflammatory–reparative imbalance. Elevated IL-18 and TNF-α indicate sustained inflammation, while reduced IL-10 and ‎altered bFGF levels reflect impaired resolution and tissue repair mechanisms. These markers, particularly bFGF, show promise as ‎potential diagnostic tools for identifying and monitoring DFU progression‎.
Keywords: Diabetes Mellitus; Diabetic Foot Ulcer; Cytokines; IL-10; IL-18; TNF-α; Bfgf.